Pemikiran Fazlur Rahman terhadap Pendidikan Islam: Pendekatan Double Movement dalam Konteks Kontemporer - Ahmad Afandi; Bagus Cahyadi (Tasqif: Journal of Islamic Pedagogy, 2025)
This study examines Fazlur Rahman's thoughts on Islamic education reform through the double movement method, which aims to integrate the historical understanding of Qur'anic revelation with its application to modern challenges. Using a descriptive qualitative approach based on literature analysis, this research explores the implementation of the method in Pakistan, Indonesia, and Malaysia. The findings show that the double movement method provides a foundation for designing a curriculum that is relevant to contemporary needs without abandoning Islamic values. In Pakistan, Rahman faced resistance from conservative groups, although his ideas continued to influence modern educational discourse. In Indonesia, the transformation of IAIN into UIN reflects the adoption of integration concepts, while Malaysia, through the International Islamic University Malaysia (IIUM), successfully adopted a holistic approach despite encountering similar challenges. This study concludes that the double movement method holds significant potential to address the challenges of globalization in Islamic education, provided it is supported by inclusive dialogue and a commitment to integrating religious values with modern knowledge.